2012
DOI: 10.1029/2012gl051205
|View full text |Cite
|
Sign up to set email alerts
|

First observations of 4fce auroral roar emissions

Abstract: This is a report on the first observations of auroral roar emissions near 4 times the ionospheric electron cyclotron frequency (fce) with a passive receiver installed in Svalbard, Norway. 4fce roar emissions were detected from 5.27 to 5.70 MHz during moderate geomagnetic disturbances in 22 days between May and September 2011 only from noon to evening, while no event occurred during the winter season. An analysis of a typical event shows that the electron density profile measured from EISCAT Svalbard dynasonde … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
14
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 19 publications
5
14
0
Order By: Relevance
“…The vast majority of the observed 4 f c e roar emissions, 86 of 88, occur during sunlit conditions, 78 of these occurring during the 6 months bracketing summer solstice (i.e., between 21 March and 21 September). This result confirms the tendency of 4 f c e roar emissions to occur in sunlit conditions as first shown by Sato et al [, Figure 3b] and confirmed by LaBelle [, Figure 2]. From this study, the occurrence rate of 4 f c e emissions in the interval 16–00 UT is approximately 5% under sunlit conditions (6006 min of 4 f c e roar in 2015 h) versus 0.06% under darkness conditions (15 min in 449 h), i.e., factor of hundreds is less likely to be observed in darkness conditions than in daylit conditions.…”
Section: Data Presentationsupporting
confidence: 91%
See 2 more Smart Citations
“…The vast majority of the observed 4 f c e roar emissions, 86 of 88, occur during sunlit conditions, 78 of these occurring during the 6 months bracketing summer solstice (i.e., between 21 March and 21 September). This result confirms the tendency of 4 f c e roar emissions to occur in sunlit conditions as first shown by Sato et al [, Figure 3b] and confirmed by LaBelle [, Figure 2]. From this study, the occurrence rate of 4 f c e emissions in the interval 16–00 UT is approximately 5% under sunlit conditions (6006 min of 4 f c e roar in 2015 h) versus 0.06% under darkness conditions (15 min in 449 h), i.e., factor of hundreds is less likely to be observed in darkness conditions than in daylit conditions.…”
Section: Data Presentationsupporting
confidence: 91%
“…As pointed out in several previous papers [e.g., Sato et al , , ; LaBelle , ; LaBelle and Dundek , ], sunlit conditions usually imply higher electron densities in the F region which allow the matching condition f u h = N f c e to occur for higher harmonics N of the electron cyclotron frequency. For this reason, generation of higher cyclotron harmonic emissions through mode conversion of upper hybrid waves stimulated at the matching condition in the presence of unstable auroral electron distribution functions occurs favorably during daytime, whereas this mechanism can directly produce only lower harmonics at nighttime when densities are lower.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Auroral roar was first detected at 2.5-2.8 MHz and associated with the harmonic of the cyclotron frequency (2f ce ) [Kellogg and Monson, 1979]. A similar emission at 3.7-4.3 MHz was associated with the 3f ce harmonic [Weatherwax et al, 1993], and recently the 4f ce harmonic was observed [Sato et al, 2012]. Satellite-borne receivers have also detected auroral roar-like signals at 1000-3000 km altitude [James et al, 1974] and much further out [Bale, 1999].…”
Section: Introductionmentioning
confidence: 98%
“…
1] Auroral radio emissions reveal physics of beam-plasma interactions and provide possibilities to remotely sense ionospheric plasma processes. Sato et al (2012) recently discovered that auroral roar emissions, long known to occur at two and three times the electron gyrofrequency ( f ce ), also occur at 4f ce . Using data from wave receivers in the British Antarctic Survey Automatic Geophysical Observatories, we confirm the existence of 4f ce -roars and observe for the first time 5f ce -roars.
…”
mentioning
confidence: 99%